PLAGIAT ADALAH DOSA: SEBUAH PERSPEKTIF ALKITABIAH TENTANG MASALAH KONTEMPORER - Alexander N. Kirk (STT BIBLIKA JAKARTA, 2020)
With the development of the internet and the proliferation of digital resources, plagiarism has become a widespread problem in academic contexts throughout the world. However, this article will argue that Christians should consider plagiarism to be a sin—that is, a moral issue and not only an academic issue. After a brief history and description of plagiarism, six reasons will be offered in support of the notion that plagiarism is a sin. Then, a potential objection will be addressed, and a few concluding remarks will be given.